PERANAN ALIANSI JURNALIS INDEPENDEN PEKANBARU DALAM MENSOSIALISASIKAN LITERASI BERITA DI KOTA PEKANBARU - Yuri Yolanda; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Technological developments are becoming very fast in the current era of globalization, especially in telecommunication media. The process of exchanging messages becomes very easy to do with the support of the internet network. However, the development of information technology today raises things that have a positive and negative impact, especially on online media. This study aims to find out how communication strategies and implementation of AJI Pekanbaru in conducting socialization activities about news literacy in Pekanbaru City. This research uses qualitative research methods with 3 informants selected through purposive technique. Data collection is done through observation, interview and documentation. To test the validity of the data writer used the method of extension of participation and triangulation. The results of this study indicate that as an organization engaged in the press, AJI has an important role in providing an understanding of news literasi especially in Pekanbaru City. AJI communications strategies such as by determining the audience who became participants in the activities to be held, determine the media strategy to help disseminate information from the activities to be held, preparing strategy messages or materials that will be described in the activity and determine the communicator strategy that is choosing someone who are competent to deliver material in accordance with the activities that have been declared. Implementation of AJI Pekanbaru in socialization is divided into two types, namely formal and informal. Implementation of socialization on news literacy in the formal form conducted by AJI Pekanbaru in seminars or workshops held by AJI or other agencies that make AJI as a resource in its activities. Socialization in informal form conducted by AJI Pekanbaru in the form of relaxation discussion with citizen journalism and some journalistic organization that exist in school and at university in Pekanbaru City.